No Due Effect or Precedence in Application for EEA Law?: Iceland’s Problematic Implementation of Protocol 35 to the EEA Agreement - Jón Sigurðsson 1991- (2020)
This thesis is centred on the implementation of Protocol 35 to the EEA Agreement in Iceland. Protocol 35 contains a rule requiring the EEA EFTA states to introduce a statutory provision into their domestic law if necessary, which affords implemented provisions of EEA law precedence vis-à-vis conflicting domestic rules. As has been extensively noted in the literature, Article 3 of the Icelandic EEA Act no. 2/1993, which is meant to implement Protocol 35, contains a rule of interpretation rather than the prescribed rule of conflict. There is however some ambiguity regarding the substance of Article 3 of Act no. 2/1993 because of what is contained in the accompanying travaux préparatoires. In the light of a number of judgments of the Icelandic Supreme Court, arguably leading to the opposite effect of what is envisioned by Protocol 35, the EFTA Surveillance Authority sent Iceland a letter of formal notice, starting a formal infringement procedure against Iceland for its improper implementation of Protocol 35. Using this letter of formal notice as a springboard, an extensive overview of the most relevant factors was undertaken with the purpose of analysing Protocol 35 and its implementation in Iceland as well as the infringement procedure. The problems outlined are chiefly considered both from the EEA law and Icelandic law perspectives. The research is based on a review of the relevant literature as well as EEA legislation and its interpretation by the EFTA Court and the Icelandic Supreme Court. EU law and case law of the Court of Justice of the European Union is also considered as well as a brief comparison with the law of the other EEA EFTA states, Liechtenstein and Norway. The central objective is to predict the most likely outcome of the infringement procedure, both in the short and long term. The outcome of a potential infringement case before the EFTA Court is considered and it is assessed whether and how Iceland is likely to comply by amending domestic legislation. The potential consequences of the alleged ...